Liquid Fuel From Polypropylene Plastic Wastes with Bentonite as Catalyst by Catalytic Cracking Process - Kurnia, Dwi Miftha; Faizal, Muhammad (ALKIMIA, 2021)
Abstract. The aim of this project work is to convert waste plastics into useful fuel range hydrocarbon mixture. The catalytic cracking process of polypropylene plastic waste (mineral water cup) was performed in a fixed-bed reactor with bentonite catalyst, at five temperatures ranging from 150 to 350oC with percent catalyst of 4%.The amounts of liquid fuel produced, as well as the compositions of the resulting liquid fuel, were determined by Gas Chromatography-Mass Spectrometry. The influences of cracking parameters, such as temperature and catalyst mass, on product yields were investigated. The optimum conditions cracking of polypropylene plastics waste with bentonite as catalyst is at temperature of 350oC with 4% catalyst mass or20 grams. The highest liquid yield (41.5%) was obtained using 20 gram Bentonite catalyst at 350oC. The highest percent composition of C6H14, C7H16 andC8H18 in liquid product is 16.92%, 18.48%, and 12.22% respectively at temperature of 350oC.